TRAJECTORIES OF BLOOD PRESSURE, TREATMENT PATTERNS AND HYPERTENSION CONTROL IN PATIENTS WITH LUPUS NEPHRITIS – DATA FROM A RETROSPECTIVE COHORT STUDY. (June 2022) - Knezevic, Tamara; Padjen, Ivan; Laganovic, Mario; Ivkovic, Vanja; Biloglav, Zrinka; Jezic, Ivana; Prlic, Margareta Fistrek; Cerovec, Mislav; Rukavina, Kresimir; Zivko, Marijana; Bulimbasic, Stela; Coric, Marijana; et al.
Abstract : Objective: Prevalence of hypertension seems to be higher in patients with systemic lupus erythematosus (SLE) than in the general population, but there is scarce data on the epidemiology of hypertension in lupus nephritis (LN). Furthermore, to the best of our knowledge, there are no studies examining the trajectories of blood pressure (BP), treatment patterns and control of hypertension in LN. Design and method: We have conducted a retrospective cohort study to evaluate the prevalence, treatment and control of hypertension in patients with biopsy-proven LN. We have collected data on demographics, clinical and laboratory parameters, histopathology and office BP measurement at the time of biopsy and after long-term follow-up. BP measurement and definition of hypertension were according to 2018 ESC/ESH guidelines. Results: A total of 36 patients with biopsy-proven LN were followed up for 4.5 ± 2.9 years (81% women, mean age at biopsy 38 ± 14). Mean duration of SLE prior to biopsy was 4.3 years (min-max 0 to 27 years). Both systolic and diastolic BP decreased from the time of biopsy to last follow-up (137/85 mmHg vs. 125/79 mmHg, p < 0.001 for systolic BP and p = 0.075 for diastolic BP). Prevalence of hypertension at the time of biopsy was 58% and increased to 72% at the time of last follow-up (p = 0.22). Mean number of drugs per patient did not change (2.0 vs. 1.8, p > 0.05). Only 48% and 58% of patients with hypertension had achieved BP control (p = 0.67) and a total of 1 and 2 patients had resistant hypertension at the time of biopsy and at last follow-up, respectively. When examining treatment, 67% and 77% patients with hypertension had an ACEI/ARB, while 48% and 38% had calcium channel blocker, 43% and 35% had diuretics and 24% and 31% had beta blockers at the time of biopsy and follow-up, respectively. Conclusions: LN is associated with high cardiovascular risk and mortality as well as a high prevalence and inadequate control of hypertension. Achieving BP control is crucial and should be an important therapeutic goal in these patients.